2008
DOI: 10.1007/s11420-007-9060-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Dislocation Rate in Ceramic-on-Ceramic Total Hip Arthroplasty

Abstract: Wear debris from metal-on-polyethylene articulation in conventional total hip arthroplasty (THA) may limit THA longevity. Bearing surfaces made of modern ceramic material, with high wear resistance and low fracture risk, have the potential to extend the longevity of THA and make the procedure more suitable for young, active patients. Concerns regarding a ceramic-on-ceramic bearing surface have included potential for a higher incidence of dislocation caused by limited modular neck length and liner options. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
(31 reference statements)
1
11
0
1
Order By: Relevance
“…Recognition of squeaking in ceramic articulations as a clinical problem has increased recently [16,17,31] with its incidence ranging from 0.48% to 7% [11,18,32]. Squeaking has been shown to be due to ceramic or metal wear, component factors, implant design, impingement, implant positioning [11,18], and patient characteristics [27]. Squeaking often occurs in younger, heavier, and taller patients [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of squeaking in ceramic articulations as a clinical problem has increased recently [16,17,31] with its incidence ranging from 0.48% to 7% [11,18,32]. Squeaking has been shown to be due to ceramic or metal wear, component factors, implant design, impingement, implant positioning [11,18], and patient characteristics [27]. Squeaking often occurs in younger, heavier, and taller patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…These enhanced mechanical properties should decrease the ceramic fracture rate, allowing the manufacturing of thinner acetabular liner inserts and therefore the use of larger femoral head options. This increased head size should improve joint stability and reduce dislocation rates [18,19]. One study also suggests that material properties of the AMC may lead to a different wear response and may decrease or eliminate squeaking [17].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Concerns of a higher dislocation rate due to limited availability of options for neck length and the liner have been noted, but no study has demonstrated a higher dislocation rate or revision due to dislocation with these bearing surfaces. [30][31][32] One review looked at the differences in forces required to dislocate THRs in vitro. 33 No difference was found in stability between different bearing surfaces where the components were implanted in the optimal position.…”
mentioning
confidence: 99%
“…In another study that reviewed 336 ceramic‐on‐ceramic THAs, Mai et al . demonstrated an early dislocation rate of 0.6% . In a multi‐centre study by Barnett et al .…”
Section: Discussionmentioning
confidence: 95%